ChemInform Abstract: Enantioselective Rh‐Catalyzed Domino Transformations of Alkynylcyclohexadienones with Organoboron Reagents. Issue 26 (6th June 2013) - Keilitz, Juliane; Newman, Stephen G.; Lautens, Mark
Abstract Title reactions proceed with moderate to good enantioselectivities.